Resurrections before the Resurrection in the Imaginaire of Late Antiquity - Shanzer, Danuta Renu (The Biblical Annals, 2019)
This paper is a study of transformations and mutations of a natural human desire, to be buried in one grave with one’s beloved. Most partners don’t die simultaneously, and burial-practices needed to provide flexibility for the dead and for the living. At the same time, religions had Views about the grave and the afterlife, and about the survival of the individual. Judaism and especially Christianity featured an astonishing doctrine, the Resurrection of the Flesh. Starting from Roman antiquity and in its epitaphic practices, the paper analyzes an intriguing early 4th C. Gallic poem, the Carmen de Laudibus Domini and its account of how the corpse of a dead woman was momentarily reanimated to greet her husband’s corpse. The poem reworks the resurrection of Lazarus with a little help from Juvencus. But a crucial (and unrecognized) source is (perhaps indirectly) Tertullian’s De Anima. These texts somehow generated a Late Antique urban legend about the mini-Resurrections of lovers’ bodies than can be traced into the central Middle Ages and beyond. It proved astonishingly lively and adaptable—to mariages blancs, to homosocial monastic situations, and to grave robbery, to name a few. This deeply sentimental legend needed to elbow aside darker phenomena, charnel (and also erotic) horrors from the pagan past, including zombies, vampires, and revenants, in order to preach its Christian message and help lovers who had been separated by death. Such resurrections were a down-payments on The Resurrection.